Cognition can affect perception: Restating the evidence of a top-down effect. (2016) - Levin, Daniel T.; Baker, Lewis J.; Banaji, Mahzarin R.
Abstract: We argue that Firestone & Scholl (F&S) provide worthwhile recommendations but that their critique of research by Levin and Banaji (2006) is unfounded. In addition, we argue that F&S apply unjustified level of skepticism about top-down effects relative to other broad hypotheses about the sources of perceptual intelligence.